An Analysis of Mantra Used by Sandro in Batanak at Tarusa Village - Solihin, Solihin; Sartika, Sartika; Juliadi, Ismail (STKIP Yapis Dompu, 2022)
Based on this background, the problems studied in this research are: (1) How is the structure of the spell used by Sandro in the Batanak. (2) What is the meaning of the mantra used by Sandro in Batanak. (3) What is the function of the mantra used by Sandro in Batanak. This study used descriptive qualitative method. Data collection techniques were video recording, interview and documentation. The researchers analyzed the data through the following steps: (1) The data obtained from video recording was analyzed by descriptive qualitative method, (2) The researchers transcribed the video recording, (3) The researchers analyzed the transcription of the video recording contained in the Batanak mantra, (4) Then clarified and described the structure, meaning and functions of the Batanak mantra. Based on the results of the analysis, it can be concluded that the structure of meaning contained in the Batanak mantra has six components, namely the title, opening, intention, suggestion, purpose and closing components. The Batanak mantra has two meanings, namely denotative and connotative, although not all of the denotative meanings have connotative meanings. The languages used in the mantra are Arabic and the Sumbawanese. Then the functions contained in the mantra are based on the expectations of a group of people who are members of the ritual, namely praying for rain.